Incêndios criminosos em edificações: um estudo sobre as medidas de prevenção e proteção - Silva, Amanda Thaís Queiroz da (Universidade Federal Rural do Semi-Árido, 2017)
The quick growth of large urban centers has had a number of consequences, including the occurrence of catastrophic fires. Faced with this picture, the fires have become a real problem for society, causing irreparable losses of all kinds. Due to the seriousness of the effects of these events, the study and investigation of them are of fundamental importance for the elucidation of possible crimes, considering that many are intentional. In this perspective, this work approaches a study on criminal fires, discussing the use of accelerators, the main agents used in events of this type, as well as prevention and protection measures used in buildings against their occurrence. Finally, a case study is presented, in which the correct implementation of the fire safety measures in a building of the commercial type is analyzed, starting from the fire project of the same one.
Keywords: Incêndios Criminosos; Criminal Fire; Acelerantes; Accelerators; Investigação; Investigation; Medidas de Segurança contra Incêndio; Fire Safety Measures; ENGENHARIAS::ENGENHARIA CIVIL